NMDA receptors antagonists alleviated the acute phase of traumatic brain injury - Mehrdad Hajinejad; Ahmadreza Gharaeian Morshed; Abdolreza Narouiepour; Maryam Izadpanahi; Mohammad Mahdi Taheri; Mohammad hossein Sadeghian; Fatemeh Forouzanfar; Sajad Sahab Negah (Iranian Journal of Basic Medical Sciences)
Objective(s): Traumatic brain injury (TBI) is a significant cause of mortality and disability worldwide. TBI has been associated with factors such as oxidative stress, neuroinflammation, and apoptosis, which are believed to be mediated by the N-methyl-D-aspartate (NMDA)-type glutamate receptor. Two NMDA receptor antagonists, ketamine and memantine, have shown potential in mitigating the pathophysiological effects of TBI.Materials and Methods: To conduct the study, a controlled cortical impact model was used to induce TBI in rats. The rats with TBI were then divided into three groups: a group receiving only TBI, a group receiving TBI along with memantine, and a group receiving TBI along with ketamine. After 24 hr, the levels of oxidative stress markers (such as SOD, MDA, and total thiol) in the brain tissue were measured. Immunohistochemical staining was also performed seven days after TBI to assess the activation of glial cells and the TLR-4/NF-κB neuroinflammatory pathway.Results: The results indicated that treatment with memantine led to a reduction in MDA levels and an increase in SOD and total thiol levels. Memantine also decreased astrogliosis and down-regulated the TLR-4/NF-κB pathway. On the other hand, ketamine increased the levels of anti-oxidant markers but did not significantly affect the MDA level. Additionally, ketamine decreased the expression of NF-κB seven days after TBI.Conclusion: The findings suggest that NMDA receptor antagonists, such as ketamine and memantine, may have therapeutic effects on TBI by inhibiting oxidative stress and inflammatory responses.